Irritating Experiments Haller's Concept and the European Controversy on Irritability and Sensibility, 1750-90 - Steinke, Hubert (Clio Medica, 2005)
One of the great medical controversies of the Enlightenment was the European debate on motion, sensation, and animal experimentation provoked by Albrecht von Haller's treatise on irritability and sensibility (1752). Irritating Experiments is the first full-length study to explore the theoretical background and the experimental process that led to Haller's description and separation of two fundamental bodily qualities: irritability, or the capacity of muscles to contract upon stimulation, and sensibility, or the capacity of the nervous system to transmit impressions that are felt as touch or pain in humans, or produce signs of pain in animals. This new concept presented a serious challenge to the reigning medical systems. Haller's animal experiments were repeated all over Europe, on a scale never seen before. The results, however, were contradictory. Haller's concept was largely rejected, and animal experimentation could not be established as a major research method in physiology. Focussing on procedural aspects of experimentation, the interaction between experiment and theory, the status of surgery, the use of medical and pathological models, and the culture of criticism, Irritating Experiments tries to explain why.